ECONOMIC IMPACT OF HANDLOOM INDUSTRIES IN TRIVANDRUM DISTRICT WITH SPECIAL REFERENCE IN BALARAMAPURAM TOWN (International Journal of Food and Nutritional Sciences, 2022)
Handloom industries in Trivandrum district play an important role for the economic impact of Trivandrum district. Handloom products in Balaramapuram region have a unique in the world. The number of handloom workers in the middle of 2009-2010 and 2019-2020 has grow by 11.5% with the comparatively expanded in total handloom production. This industry increase our GDP and also our foreign exchange earnings. about 16% of fabric production in India is from the handloom industry. This paper concentrates about the economic impact of handloom industries in Balaramapuram Town.